Decriminalization of the act of managing in light of Presidential Instruction 02-2021 - Harkati, Djamila (Journal of Human Sciences, 2022)
Through this research paper, we shed light on the Presidential Instruction No. 02-2021 related to the protection of local managers, which included a set of mechanisms to decriminalize the act of managing because of its importance in instilling confidence in these managers and reviving the national economy. We also analyzed the legal dimensions and effects. For this presidential instruction on managers and the national economy by studying the effectiveness of the presidential instruction in this field, and the most important practical problems for implementing the policy of decriminalizing the act of management were identified.